The Rule of Law, Religious Authority, and Oaths of Office - Aroney, Nicholas (Journal of law, religion and state, 2018)
The rule of law requires political office holders to exercise their powers in accordance with the law. Most societies, however, rely not only on the moral obligation to obey the law but also require office holders to take a religious oath or solemn affirmation. The divine witness to the oath of office stands in as a guarantor of the political order but also looms above it. As such, the oath represents a paradox. It guarantees the performance of official duties while also subjecting them to external judgement. The oath thus encompasses the large question of the relationship between religious conviction, personal fidelity, moral principle, and political power. It suggests that law and religion are as much intertwined as separated in today’s politics. By tracing the oath of office as a sacrament of power, much light can be shed on the relationship between law and religion in today’s liberal-democratic politics.